The Cyclical Behavior of Interest Rates. - Roma, Antonio; Torous, Walter (Journal of Finance, 1997)
This article investigates the behavior of the term structure of interest rates over the business cycle. In contrast to prior studies that measure the business cycle by the simple growth in aggregate economic activity, the authors consider the deviation of aggregate economic activity from its potentially stochastic trend. They show that incorporating both an independent trend and cyclical component in consumption improves the efficiency in estimating consumption-based asset pricing models. The authors also find that the term spread is more informative about future changes in stochastically detrended real gross domestic product (GDP) than future growth rates in real GDP.